GLOBAL DIGITAL DEATH AND GLOCAL DYING: THEORETICAL CHALLENGES AND POSSIBLE RESEARCH DIRECTIONS: (Glocalism: Journal of Culture, Politics and Innovation, 2024)
This paper discusses the possibilities of using theories of glocalisation for understanding national differences in death ways, in times when global digital technologies play a growing role in how individuals and societies respond to severe crises. How people approach death is influenced by personal needs and values, unfolding within a thick framework of significance. Romania is a revealing example: what it is locally relevant is not unproblematically linked to a global pattern. After exploring the literature, we identify and discuss three key-directions of research that may be of help in further debates: 1. glocalisation of lived death practices and meanings; 2. glocalisation of death studies agendas; 3. the theoretical relevance of glocalism for understanding fundamental human experiences (we suggest a social phenomenological approach).
Keywords: death studies; glocal studies; digital technologies; global consciousness; Romania